The Influence of Product Quality, Perception of Spare Parts Prices, and Brand Awareness on Customer Loyalty of Yamaha Vixion Motorcycles in East Java - Rumy, Jalalludin; Ikaningtyas, Maharani (Universitas KH. Abdul Chalim Mojokerto, 2025)
The Indonesian automotive sector continues to grow, as reflected in the increasing demand for vehicles, especially motorcycles. Yamaha Vixion has become a popular sport motorcycle choice that combines a sporty appearance with riding comfort across various road conditions. This study aims to analyze the influence of Product Quality, Spare Part Price Perception, and Brand Awareness on Customer Loyalty toward Yamaha Vixion in East Java. A quantitative method was applied, involving 150 respondents aged 19 and above who have purchased or used a Yamaha Vixion. The sampling technique used was purposive sampling based on specific criteria. Data were processed using multiple linear regression with SPSS version 26. The results indicate that Product Quality, Spare Part Price Perception, and Brand Awareness simultaneously have a significant effect on Customer Loyalty.